R n = k = 0 ∑ n ( k 2 k ) , S n = k = 0 ∑ n ( − 1 ) k ( k 2 k )
For n belonging to the set of non-negative integers, define R n and S n as of above. Also define A n and B n as:
A n = R n 2 + 2 k = 1 ∑ n ( n + k 2 n + 2 k ) R n − k
B n = S n 2 + 2 k = 1 ∑ n ( − 1 ) n + k ( n + k 2 n + 2 k ) S n − k
Evaluate the value of: lo g 2 ( 5 B 2 0 1 5 − 3 A 2 0 1 5 ) upto three correct places of decimals.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
It is well known that the generating functions for the sequences ( k 2 k ) and ( − 1 ) k ( k 2 k ) for k = 0 , 1 , 2 , … are 1 − 4 x 1 and 1 + 4 x 1 respectively, i.e
1 − 4 x 1 = k = 0 ∑ ∞ ( k 2 k ) x k and 1 + 4 x 1 = k = 0 ∑ ∞ ( − 1 ) k ( k 2 k ) x k
1 − 4 x 1 ⋅ 1 − 4 x 1 = 1 − 4 x 1 = k = 0 ∑ ∞ ( 4 x ) k
We conclude that A n = 1 + 4 + 4 2 + … + 4 2 n = 3 1 ( 4 2 n + 1 − 1 )
Similarly, we can show for B n that B n = k = 0 ∑ 2 n ⎝ ⎛ i + j = k ∑ ( − 1 ) k ( i 2 i ) ( j 2 j ) ⎠ ⎞ . . . ( 2 )
and that the coefficients on the right hand side on (2) is precisely the coefficients of x 0 , x 1 , x 2 , … , x 2 n in the product of k = 0 ∑ ∞ ( − 1 ) k ( k 2 k ) x k .
Since 1 + 4 x 1 ⋅ 1 + 4 x 1 = 1 + 4 x 1 = k = 0 ∑ ∞ ( − 1 ) k ( 4 x ) k , we conclude that B n = 1 − 4 + 4 2 − 4 3 + … + 4 2 n = 5 1 ( 4 2 n + 1 + 1 )
Thus 5 B n − 3 A n = 2 for all n belonging to non-negative integers. Thus our answer is lo g 2 ( 2 ) = 1 . 0 0 0 .